Twin gestation with complete hydatidiform mole and a coexisting live fetus: case report and brief review of literature - Makary, Raafat (Obstet Med, 2010)
Complete hydatidiform (also referred to as hydatiform) mole with coexisting live fetus is an exceedingly rare event. The fetus usually has a normal karyotype, and approximately 25–40% chance of survival, if pregnancy is allowed to continue until reasonable fetal lung maturity is achieved. However, risk of maternal complications including preeclampsia and subsequent trophoblastic disease are significant. We report a case of a 19-year-old primigravida, at 25 weeks gestation with a complete hydatidiform mole and a coexisting live fetus. She developed severe preeclampsia with uncontrolled hypertension, and pregnancy was terminated by caesarean section, after a short course of dexamethasone to accelerate fetal lung maturity. A morphologically normal live female fetus and placenta were delivered without complications, along with a separate mass of complete mole. The postpartum course was complicated by uterine choriocarcinoma with metastases to lung and left kidney, which responded to chemotherapy. Our case is a rare example of a twin gestation composed of a complete hydatidiform mole with a coexisting live fetus, and illustrates the associated spectrum of maternal complications that mandate close pre- and post-natal surveillance.